Nilai-Nilai Bela Negara Dalam Buku PAI : Analisis Isi Buku - Yuliandre, Yuliandre; Hadiyanto, Andy; Amaliyah, Amaliyah (Jurnal Studi Al-Qur’an, 2019)
This paper purpose to discuss matters of state defense, methods and techniques of presentation in the book of Islamic Higher Education level. The values of state defense include proud of the homeland, the awareness of the nation and the state, convinced that Pancasila as the state ideology, the willingness to sacrifice for the nation and state and have basic ability to defend the country. This research approach uses an analytical approach to analyze the value of state defense in the book of Islamic Education published by the Ministry of Education and Culture, Erlangga, and Yudhishthira. This research produces some important things about the values of state defense which is presented in the book of Islamic Education and its presentation technique. Keywords: Values, State Defense, High School PAI Book Abstrak Penelitian ini bertujuan untuk membahas nilai-nilai bela negara, metode dan teknik penyajiannya dalam buku Pendidikan Agama Islam tingkat SMA. Nilai-nilai bela negara meliputi kecintaan terhadap tanah air, kesadaran berbangsa dan bernegara, yakin Pancasila sebagai ideologi negara, kerelaan berkorban untuk bangsa dan negara serta memiliki kemampuan awal bela negara. Pendekatan penelitian ini menggunakan pendekatan analisis isi untuk menganalisa nilai-nilai bela negara dalam buku Pendidikan Agama Islam terbitan Kementerian Pendidikan dan Kebudayaan, Erlangga, dan Yudhistira. Penelitian ini menghasilkan beberapa hal penting tentang nilai-nilai bela negara yang disampaikan dalam buku Pendidikan Agama Islam dan teknik penyajiannya. Kata Kunci: Nilai-Nilai, Bela Negara, Buku PAI SMA